2005
DOI: 10.1007/11596042_96
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of a Generalized Anonymous Buyer-Seller Watermarking Protocol of IWDW 2004

Abstract: Abstract.In this paper, we analyze the security of a generalized anonymous buyer-seller watermarking protocol recently proposed by Choi and Park at IWDW 2004. We prove that it has not met the designers' intended security criteria by showing that an attacker can actually: (1) discover the unique buyer's watermark which was chosen by the watermark certificate center (W CC), and (2) decrypt the encrypted watermarked digital content without any extra cost. Also, it is surprising to note that when designing their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We caution against simple fixes that patch our attacks in this paper since experience has shown that the break-and-fix cycle loops indefinitely, for instance see [17][18][19][30][31][32] where attacks were applied to protocols [8-11, 20, 22, 6, 36] that improved on existing ones. We suggest instead, that if BSW schemes are required, to consider other schemes like [24,38] that have not yet been shown to fall to any attacks that counter their design goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We caution against simple fixes that patch our attacks in this paper since experience has shown that the break-and-fix cycle loops indefinitely, for instance see [17][18][19][30][31][32] where attacks were applied to protocols [8-11, 20, 22, 6, 36] that improved on existing ones. We suggest instead, that if BSW schemes are required, to consider other schemes like [24,38] that have not yet been shown to fall to any attacks that counter their design goals.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a few subsequent BSW schemes proposed with different additional features like anonymity [20], without trusted third parties (TTP) [10] and extension for multiple purchases [11] were later found to have security problems [10,19,18]. A few more recent schemes can be found in [24,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…[14] presented a protocol that also protects the buyer's privacy. Several buyer-seller protocol variants have been constructed since then, including the protocols proposed in [1], [2], [5], [6], [8], [9], [12], [13], [15], [16], [17], [21], and subsequent analyses appear in [10], [11], [20], [24], [5,4,23].…”
Section: Buyer-seller Watermarking Protocolsmentioning
confidence: 99%